Left-sided hemianopia as an unrecognized symptom of brain tumor and head injury - Obuchowska, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Homonymous hemianopia (HH) is a visual field defect characterized by the involvement of two right or left halves of the visual field in both eyes. Patients with HH complain of difficulties with reading and scanning scenes in sufficiently rapid fashion to make sense of things as a whole. Some of these patients are not aware of their visual field defect. We report two cases of left-sided hemianopia in which visual field defects were detected “quite” accidentally. In the case of the first patient, revealing HH facilitated the detection of brain tumor and its treatment. In the case of the other patient, identifying HH, which was caused by a head injury, and making the patient aware of this fact, prevented potential harmful consequences associated with driving a car by a person with severe deficits in cognitive visual functions.